Mediating role of sleep quality in the relationship between diabetes mellitus and visual function: a cross-sectional study - Yingrui Yang; Xiaoting Pei; Jiali Sun; Mengting Xia; Lina Tian; Yanxia Kang; Zhijie Li (Scientific Reports)
Abstract Diabetes mellitus (DM) is a major global health concern associated with complications that significantly impair quality of life. Among these, the impact of DM on visual function and the underlying mechanisms, particularly the role of sleep quality, remain insufficiently understood. This cross-sectional study recruited 629 participants from Henan Provincial People’s Hospital to examine the relationships among DM, sleep quality, and visual function. Visual function was assessed using the National Eye Institute Visual Function Questionnaire-25 (NEI-VFQ-25), while sleep quality was evaluated with the Pittsburgh Sleep Quality Index (PSQI). Compared to non-diabetic controls, individuals with DM exhibited significantly poorer visual function and sleep quality. Path analysis further revealed that sleep quality played a significant mediating role in the relationship between DM and visual function, accounting for 42.2% of the total effect. Subgroup analyses indicated that female and elderly patients with DM were more susceptible to the influence of sleep disturbances on visual outcomes. These findings underscore the critical role of sleep quality in diabetes-related visual impairment and highlight the importance of incorporating routine sleep assessments and targeted interventions into diabetes management to help preserve visual function and improve overall quality of life in diabetic populations.